Low-income mothers' perspectives on the involvement of family members in child feeding. (1st January 2022) - Quinn, Martha; Herty, Lauren; Weeks, Heidi M.; Kwan, Janice; Haines, Jess; Bauer, Katherine W.
Abstract: Nearly all research on child feeding has focused on mothers. Very little is known about other family members' roles in feeding children nor how mothers engage with these family members regarding child feeding. The objective of this study was to examine mothers' perceptions of other family members' child feeding roles and practices within low-income families, including the challenges experienced and strategies employed by mothers when sharing responsibility for child feeding. Low-income mothers (n = 100) of pre-adolescent children participated in semi-structured interviews regarding child feeding including shared responsibility for child feeding. A content analysis was then conducted to identify main themes in mothers' responses, with three main themes arising from the interviews. First, many family members were actively involved in child feeding and food-related decision-making. The majority of mothers (85%) reported that another family member was involved in feeding their child including fathers and father figures, who were involved in feeding in 63% of families. Other family members, mainly grandparents, were involved in feeding in 35% of families. Mothers identified several concerns regarding their child's eating when with other family members, particularly when grandparents fed children. Finally, mothers employed several strategies to control their children's eating when children were cared for by other family members. Future interventions to promote healthy child feeding among low-income families may benefit from helping mothers negotiate child feeding with other family members, particularly grandparents, and supporting family members' engagement in child feeding.